Action verbal fluency in parkinson’s patients - Rodrigues, Inês Tello (2021)
We compared the performance of 31 non-demented Parkinson’s disease (PD) patients to 61 healthy controls in an action verbal fluency task. Semantic and phonemic fluencies, cognitive impairment and behavioural dysfunction were also assessed. The mean disease duration of PD was 9.8 years (standard deviation (SD) = 6.13). There were no age (U = 899.5, p = 0.616), gender(chi-square = 0.00, p = 1.00) or literacy (U = 956, p = 0.96) differences between the two groups. A significant difference was observed between the two groups in the action verbal fluency task (U = 406.5, p < 0.01) that was not found in the other fluency tasks. The education level was the only biographical variable that influenced the action (verb) fluency outcomes, irrespective of disease duration. Our findings suggest a correlation between the disease mechanisms in PD and a specific verb deficit, support the validity of the action (verb) fluency as an executive function measure and suggest that this task provides unique information not captured with traditional executive function tasks.